Digestive enzyme activity of the Japanese grenadier anchovy Coilia nasus during spawning migration: influence of the migration distance and the water temperature. Issue 5 (14th October 2019) - Ma, Fengjiao; Yang, Yanping; Jiang, Min; Yin, Denghua; Liu, Kai
Abstract: In this study, we investigated the activity levels of two major digestive enzymes (pepsin and lipase) in the commercially important Japanese grenadier anchovy Coilia nasus during its upstream migration to analyse the digestive physiological responses to starvation and to analyse the influence of the water temperature on enzyme activity. Water temperature had a significant effect on pepsin activity, while long‐term starvation resulted in a significant decrease in pepsin activity. As starvation continued, however, a slight increase in pepsin activity between the Wuhu (440 river km) and Anqing (620 river km) regions may indicate that C. nasus had refeeding behaviour due to its large expenditure of energy reserves. In contrast, lipase activity was not significantly affected by the water temperature but the effect of fasting increased as much as 13% of lipase activity from the Chongming region (20 river km) to Anqing region, suggesting that the stored lipids of grenadier anchovy were mobilised to meet energy requirements of upstream migration activity and gonad development. Lipid mobilisation activated lipoprotein lipase (LPL; proteins with lipase activity) to hydrolyse triacylglycerides (TAG), which is the first step of lipid assimilation and obtained energy from fatty acids under fasting conditions. Therefore, the increased lipase activity is attributed mainly to the lipase that is involved in endogenous lipid hydrolysis. Grenadier anchovy appears to adapt to long‐term starvation during migration and the increased lipase activity may indicate a crucial effect on lipid metabolism. This study demonstrated that distinct alterations occur in pepsin and lipase activities during the spawning migration of grenadier anchovy due to exogenous nutrition and endogenous metabolism. Furthermore, it provides a basis for further research on the digestive physiology and energy metabolism in this species.